A Case Study to Establish a Basis for Evaluating Geographic Origin Claims of Timber From the Solomon Islands Using Stable Isotope Ratio Analysis - Watkinson, Charles J.; Rees, Gareth O.; Hofem, Sabine; Michely, Lina; Gasson, Peter; Boner, Markus (Frontiers in Forests and Global Change, 2022)
Global demand for low-cost forest products is leading manufacturers and traders to source timber and wood products from vulnerable nations and delicate ecosystems. One small island nation, the Solomon Islands, is seeing exploitation of natural resources accelerating to such a point that its natural forests may be exhausted by 2036. The main causes of natural forest loss on the archipelago are unsustainable or illegal logging practices. Various laws in consumer countries require that members of industry ensure that only legally sourced timber is placed onto their respective national markets. Those that break these laws or fail to act in a way that is compliant may be subject to harsh penalties. This study aims to establish scientific data to evaluate claims that timber has originated from the Solomon Islands. This will enable Operators to carry out due diligence analysis and permit members of Law Enforcement to conduct forensic investigations. Eighty timber core samples comprising thirteen different genera of tropical trees were obtained from mature trees in two sites in the Solomon Islands (Guadalcanal and Kolombangara islands) during the period August 2019 to November 2019 using a Pickering Punch sampling device. Homogenised core samples were subject to δ18O, δ2H, δ13C, and δ34S stable isotope analysis using elemental analysis-isotope ratio mass spectrometry (EA-IRMS). Additional stable isotope data from relevant taxa and geographic origins (elevation, geographic co-ordinates) were also included in this research as an initial assessment of differences in stable isotope ratios between countries. Results show that significant differences are evident in the stable isotope ratios of the sampled taxa within the Solomon Islands (Guadalcanal and Kolombangara Islands) and between other countries. These data can be used as a basis of evaluation to evaluate origin claims of timber or wood products from the Solomon Islands, particularly Kolombangara Island. Furthermore, in the right context, these data can also be used to establish whether timber or wood products declared to be from origins other than the Solomon Islands have stable isotope ratios that are consistent with data from the Solomon Islands. If not, this would suggest foreign timber/forest products are from elsewhere.